2014
DOI: 10.1016/j.gene.2014.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tris(2,3-dibromopropyl) isocyanurate on the expression of photosynthesis genes of Nannochloropsis sp.

Abstract: a b s t r a c t a r t i c l e i n f oThe proteins encoded by psaA and psaB form a heterodimer, an essential compound of photosystem; while the protein encoded by psbC binds with chlorophyll a in photosystem II, serving as antennae in photosystem. Here we report that a heterocyclic brominated flame retardant, tris(2,3-dibromopropyl) isocyanurate (TBC), inhibited the expression of psaA and psbC, then leads to the decrease of Nannochloropsis sp.'s growth biomass. TBC exposure inhibited the expression of psaA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…We also measured TBC in our samples. TBC also belongs to the triazine family and has been widely detected in Chinese environmental samples. , , TBC has a MW of 728.69 and it contains 6 bromines. The most abundant ion is [M–Br] +/− , for which the cluster centered at m / z 648 is visible in both ECNI and EI modes (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also measured TBC in our samples. TBC also belongs to the triazine family and has been widely detected in Chinese environmental samples. , , TBC has a MW of 728.69 and it contains 6 bromines. The most abundant ion is [M–Br] +/− , for which the cluster centered at m / z 648 is visible in both ECNI and EI modes (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…TBC was reported in abiotic and biotic samples near a manufacturing facility in China, mollusks from the Chinese Bohai Sea, sediments from Yellow River and Jiaozhou Bay of China, , and curtains from Japanese markets . TBC can cause neurotoxicity to rats, induce reproductive and endocrine toxicity in zebrafish, and prevent the growth of algae . TTBP-TAZ has been found in the plastic casings of electrical and electronic equipment and in dust samples collected in The Netherlands .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algae are water purity indicators; moreover, they are used as food for aquatic organisms, e.g., larvae, young Decrease in E 2 and testosterone levels Environ Geochem Health mollusks, and larvae of selected crustaceans and fish, influencing their growth and development (Brown & Jeffrey, 1992;Wang et al, 2014). The presence of biotic stressors influences the photosynthesis process in plants, for example by reducing the expression of genes involved in photosynthesis.…”
Section: Water Organismsmentioning
confidence: 99%
“…Wang et al investigated the effect of TBC at concentrations of 10, 100, and 1000 ng/ mL on a selected family of microalgae, i.e., Nannochloropsis sp., and demonstrated inhibition of their growth. Additionally, the authors observed a decrease in the expression of the psaA and psbC genes encoding proteins crucial for the photosystem along with the increase in the concentration used (Wang et al, 2014). The zebrafish (Danio rerio) has been found to be a suitable model organism to analyze the mechanism of action and toxicity of BFR (Usenko et al, 2016).…”
Section: Water Organismsmentioning
confidence: 99%